Echoes of Silence: The Role of Unspoken Words in Shaping Characters in John Steinbeck’s Of Mice and Men - Rasheed, Ali Hussein Ali; Safar , Mohanad; Awad, AlHasan (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2025)
John Steinbeck's novella, Of Mice and Men (1937), uses silence as a literary device to define the sociology and psychology of his central characters. This research project explores how silence contributes to characterization from a modernist and minority criticism prospective, championing the Assembled from what is not said—George Milton, Lennie Small and Curley's wife. The signifying moments of silence illustrate that silence is a presence and not an absence. Thus, via comprehensive text analysis, audiences find that George's silences are an acknowledgment of his somber duty, Lennie's failures are tragic, yet innocently, and Curley's wife's relative silence is feministically indicative of how she lived a life unheard due to societal erasure. Silence is an enforced reality that deepens meanings of loneliness, wants and inaccessible dreams. Therefore, a modernist critique applies through the fragmentation of the American Dream and the inability to voice one's contempt against depression. Quantitative resources include crucial passages from the book as well as relative support from secondary sources like Warren French and Susan Sontag that put Steinbeck's technique in context with twentieth-century literature. The findings show that silence enriches character development and multidimensional observations of real men/Women lives experienced during the Great Depression, adding an emotional resonance beyond standard comprehension. For example, the comparison of silence through Steinbeck's work relative to Hemingway's shows how sometimes, silence can speak louder than words. Ultimately, Of Mice and Men is a relative new classic that teaches silence can scream and gives research opportunities outside this one to investigate how Steinbeck utilizes silence in all his works.